Pengaruh Inovasi Produk, Pemahaman Sertifikat Halal, dan Literasi Produk Terhadap Keputusan Generasi Milenial Membeli Produk Kosmetik. - Munawaroh, Munawaroh; Syah, Muhammad Radian; Putri Silalahi, Cita Ayni; Pradesyah, Riyan (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
The development of the cosmetics world in Indonesia continues to show its graph on increasing use. Currently, many cosmetics are circulating among people who do not have halal certificates. This research aims to see the influence of product innovation, understanding of halal certificates, and product literacy on the millennial generation's decision to buy cosmetic products in the city of Medan. From the results of the study, it was found that there was a significant influence of product innovation on the millennial generation's decision to buy cosmetic products, by 57.89%. Then, there is a significant influence of the Understanding of Halal Certificate on the millennial generation's decision to buy cosmetic products, by 39.05%. And there is no significant influence of product literacy on the millennial generation's decision to buy cosmetic products